The correct answer is D. The error occurs in step 3, where the equation is simplified incorrectly. The correct simplification should be:
2x - 2 + c - b = c - b - 2
So, the correct solution is x = (c - b - 2)/2
solve the equation for x: 2x + b = c
check this process:
step 1: 2x + b - b = c - b
step 2: 2x = c - b
step 3; 2x - 2 + c - b - 2
step 4: x = c/2 - b - 2
check all of the choices that are true statements
A. there is no error in the process
B. the process has an error from step 1 to step 3
C. the process has an error from step 2 to step 3
D. the process has an error from step 3 to step 4
3 answers
are you sure that is the only answer
You are correct, I apologize for the confusion in my previous response. Actually, multiple answers could be correct for this problem. Here is the correct explanation:
In step 3, the equation simplifies to:
2x - 2 + c - b = c - b - 2
From here, we can see that the terms "-2" and "-b" on both sides of the equation cancel out:
2x - 2 + c - b = c - b - 2
Simplifying further:
2x + c - b = c - b
Now, we can subtract "c" from both sides to isolate the "x" on the left side:
2x + c - b - c = c - b - c
Simplifying:
2x - b = -b
Dividing both sides by 2:
(2x - b)/2 = -b/2
This gives us two possible solutions:
x - (b/2) = -b/2
or
x = -b/2
So, the correct answer is:
E. The process has an error in step 3, but there are multiple correct solutions depending on the value of "b."
In step 3, the equation simplifies to:
2x - 2 + c - b = c - b - 2
From here, we can see that the terms "-2" and "-b" on both sides of the equation cancel out:
2x - 2 + c - b = c - b - 2
Simplifying further:
2x + c - b = c - b
Now, we can subtract "c" from both sides to isolate the "x" on the left side:
2x + c - b - c = c - b - c
Simplifying:
2x - b = -b
Dividing both sides by 2:
(2x - b)/2 = -b/2
This gives us two possible solutions:
x - (b/2) = -b/2
or
x = -b/2
So, the correct answer is:
E. The process has an error in step 3, but there are multiple correct solutions depending on the value of "b."